PENGARUH STRATEGI HARGA PSIKOLOGIS TERHADAP NIAT PEMBELIAN KONSUMEN PRODUK PAKAIAN WANITA DI SHOPEE KOTA BANDUNG DENGAN KEPUASAN TERHADAP HARGA SEBAGAI VARIABEL INTERVENING - Amelia Zahra; Abdul Malik Sayuti (MANAJEMEN DEWANTARA, 2025)
This study aims to (1) examine the influence of psychological pricing on price satisfaction, (2) analyze its effect on purchase intention, (3) assess the impact of price satisfaction on purchase intention, and (4) evaluate the mediating role of price satisfaction in the relationship between psychological pricing and purchase intention. A quantitative method was applied, targeting Bandung residents who had purchased women’s clothing through Shopee in the past three months and were exposed to psychological pricing. Using purposive sampling, 240 respondents were selected based on the recommended sample size of 10 times the total of 24 indicators. Data were collected through a Likert-scale questionnaire covering psychological pricing, price satisfaction, and purchase intention. Findings show that psychological pricing significantly affects both price satisfaction and purchase intention. However, price satisfaction does not significantly influence purchase intention, and its mediating role in the relationship is statistically insignificant. While direct effects are evident, the indirect impact of price satisfaction remains weak. These results highlight the importance of pricing strategies in shaping consumer behavior, though not necessarily mediated by satisfaction with price.